2014
DOI: 10.5120/16362-5772
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Logic Approach to Credit Scoring for Micro Finance in Ghana: A Case Study of KWIQPLUS Money Lending

Abstract: This paper presents a fuzzy logic approach to credit scoring for Micro Finance.The research was necessitated as a result of the inability of many Micro Finance Institutions in Ghana to recover loans from their clients which is leading to their eventual collapse. It has been presumed that proper evaluations are not done by the Micro Finance Institutions thereby advancing loans to wrongful applicants. The main objective of this research was therefore to provide a Fuzzy approach to credit scoring in order to redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The study used inputs parameters such as ability to pay back, profitability, operational ability in order to predict the credit potential of the different clients. In his conclusion, he identifies fuzzy logic as one the most significant techniques in the field of machine learning especially since it's reliable, scalable and stable [10] The research found that, Fuzzy Logic is effective in modelling applications where human judgement is involved and could therefore be used in evaluating loan applications. However, the choice of variables, especially thresholds can make the model less useful if economic conditions change in the future unless the variables are adjusted.…”
Section: Literature Review 21 a Review Of Fuzzy Credit Score Modelsmentioning
confidence: 99%
“…The study used inputs parameters such as ability to pay back, profitability, operational ability in order to predict the credit potential of the different clients. In his conclusion, he identifies fuzzy logic as one the most significant techniques in the field of machine learning especially since it's reliable, scalable and stable [10] The research found that, Fuzzy Logic is effective in modelling applications where human judgement is involved and could therefore be used in evaluating loan applications. However, the choice of variables, especially thresholds can make the model less useful if economic conditions change in the future unless the variables are adjusted.…”
Section: Literature Review 21 a Review Of Fuzzy Credit Score Modelsmentioning
confidence: 99%
“…It was not until the 1970s that these credit scores became an important component of the lending industry. Many lenders, from banks to microfinance institutions, currently use credit scoring to measure a potential borrower's creditworthiness (Abdulrahman et al 2014).…”
Section: Credit Scoring In Related Industriesmentioning
confidence: 99%
“…It was proposed by Prof. Lofti Zadeh in the year 1965. It is mostly used to deal with imprecision and vagueness of human subjective judgment and represent information from zero to one [9].…”
Section: Related Workmentioning
confidence: 99%
“…Five attributes were used in the evaluation criteria. [9] Applied fuzzy logic to credit scoring in Ghana to determine the credit worthiness of applicants.…”
Section: Related Workmentioning
confidence: 99%